ANALISIS IMPLEMENTASI PLATFORM WAYGROUND TERHADAP MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA PADA MATERI BENTUK ALJABAR KELAS VII DI MTs DARUL IRFAN - Desty Endrawati Subroto; Yuke Andriani; Febriani Putri; M. Firman Syah (STAI Darul Qalam Tangerang, 2026)
This study analyzes the implementation of the Wayground platform as an interactive evaluation medium to overcome learning boredom in mathematics, specifically on Algebraic Forms at MTs Darul Irfan. The main issue addressed is the dominance of conventional, teacher-centered learning methods that trigger deep passivity and boredom among Grade VII students. Using a descriptive-quantitative method with a pretest-posttest design, this study involved 40 students as the full population, consisting of 30 male and 10 female students. The pretest results revealed an alarming class average of 33.1, with only 0 students (0.0%) meeting the Minimum Completeness Criteria (KKM). Following the implementation of the Wayground platform over two learning sessions, a significant improvement was observed in posttest scores, with the class average surging to 70.1, and as many as 21 students (52.5%) successfully exceeding the KKM. These findings confirm that Wayground integration not only effectively transforms the classroom atmosphere into a more enthusiastic and competitive environment, but also drives measurable and meaningful improvements in cognitive learning achievement.